Prototype of an alcohol monitoring for raw water supply pumps control system - Dhimas Widhy Surya Brata; Artono Dwijo Sutomo; Agus Supriyanto (Journal of Physics: Theories and Applications, 2025)
Monitoring of alcohol waste that could potentially enter the raw water intake pump of the Semanggi Water Treatment Plant (WTP) on the Bengawan Solo river is still done manually, with officer watching near the pump for 12 hours per shift. A prototype alcohol monitoring system designed to make more efficient device than manual method that needs 34,7 s to turn off the pump and finding the optimal distance between the sensor and the water pump. The working principle is automate pump control, so the water pump can automatically turn off when alcohol is detected by the sensor and turn on again when no alcohol is detected. The reaction time to turn off the pump is calculated from the time the 2 ml alcohol container is placed under the sensor until the pump turns off, while the time to turn the pump back on is calculated from the time the pump turns off until the pump turns back on. The reaction time of turning off the pump and restarting the pump at 7% alcohol percentage is 1.80 s and 0.72 s, while at 24% alcohol percentage is 0.87 s and 1.90 s. The Bengawan Solo river velocity ranges from 0.04 m/s to 0.27 m/s. Thus, this device turn off water pump time is faster by 94,8% than manual method and the optimal distance between the sensor and the water pump is more than 0.28 m and less than 0.39 m.